Dynamics of Acute Local Inflammatory Response after Autologous Transplantation of Muscle-Derived Cells into the Skeletal Muscle. (27th August 2014) - Burdzinska, Anna; Gala, Kamila; Kowalewski, Cezary; Zagozdzon, Radosław; Gajewski, Zdzisław; Pączek, Leszek
Abstract : The vast majority of myoblasts transplanted into the skeletal muscle die within the first week after injection. Inflammatory response to the intramuscular cell transfer was studied in allogeneic but not in autologous model. The aim of this study was to evaluate immune reaction to autotransplantation of myogenic cells and to assess its dynamics within the first week after injection. Muscle-derived cells or medium alone was injected into the intact skeletal muscles in autologous model. Tissue samples were collected 1, 3, and 7 days after the procedure. Our analysis revealed the peak increase of the gene expression of all evaluated cytokines ( Il-1α, Il-1 β, Il-6, Tgf- β, and Tnf-α ) at day 1. The mRNA level of analyzed cytokines normalized in subsequent time points. The increase of Il- β gene expression was further confirmed at the protein level. Analysis of the tissue sections revealed rapid infiltration of injected cell clusters with neutrophils and macrophages. The inflammatory infiltration was almost completely resolved at day 7. The survived cells were able to participate in the muscle regeneration process. Presented results demonstrate that autotransplanted muscle-derived cells induce classical early immune reaction in the site of injection which may contribute to cellular graft elimination.